Contribution of CD4+ T cells to the early mechanisms of ischemia- reperfusion injury in a mouse model of acute renal failure - Pinheiro,H.S. (2007)
Renal ischemia-reperfusion (IR) injury is the major cause of acute renal failure in native and transplanted kidneys. Mononuclear leukocytes have been reported in renal tissue as part of the innate and adaptive responses triggered by IR. We investigated the participation of CD4+ T lymphocytes in the pathogenesis of renal IR injury. Male mice (C57BL/6, 8 to 12 weeks old) were submitted to 45 min of ischemia by renal pedicle clamping followed by reperfusion. We evaluated the role of CD4+ T cells using a monoclonal depleting antibody against CD4 (GK1.5, 50 µ, ip), and class II-major histocompatibility complex molecule knockout mice. Both CD4-depleted groups showed a marked improvement in renal function compared to the ischemic group, despite the fact that GK1.5 mAb treatment promoted a profound CD4 depletion (to less than 5% compared to normal controls) only within the first 24 h after IR. CD4-depleted groups presented a significant improvement in 5-day survival (84 vs 80 vs 39%; antibody treated, knockout mice and non-depleted groups, respectively) and also a significant reduction in the tubular necrosis area with an early tubular regeneration pattern. The peak of CD4-positive cell infiltration occurred on day 2, coinciding with the high expression of ßC mRNA and increased urea levels. CD4 depletion did not alter the CD11b infiltrate or the IFN-g and granzyme-B mRNA expression in renal tissue. These data indicate that a CD4+ subset of T lymphocytes may be implicated as key mediators of very early inflammatory responses after renal IR injury and that targeting CD4+ T lymphocytes may yield novel therapies.